2016
DOI: 10.3389/fnbeh.2016.00059
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Transcription Factor Nk2 Homeobox 1 in Schizophrenia: Convergent Evidence from Animal and Human Studies

Abstract: Schizophrenia is a highly heritable disorder with diverse mental and somatic symptoms. The molecular mechanisms leading from genes to disease pathology in schizophrenia remain largely unknown. Genome-wide association studies (GWASs) have shown that common single-nucleotide polymorphisms associated with specific diseases are enriched in the recognition sequences of transcription factors that regulate physiological processes relevant to the disease. We have used a “bottom-up” approach and tracked a developmental… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 431 publications
(521 reference statements)
0
17
0
Order By: Relevance
“…Taking the literature into account, our current data suggest that the HPV vaccine may disrupt signaling pathway mediated by Nkx2.1 that are expressed in the hypothalamic region. We studied on the neurotransmitters production in order to corroborate pathophysiological correlation of Nkx2.1, since some studies indicated the abnormalities of several neurotransmitters production in Nkx 2.1 deficient-mice in early development42, and also in adult mice3538. We found similar phenotype of neurotransmitters production in group 4 mice including increase of dopaminergic neurons and reduced GABAergic neurons (Fig.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Taking the literature into account, our current data suggest that the HPV vaccine may disrupt signaling pathway mediated by Nkx2.1 that are expressed in the hypothalamic region. We studied on the neurotransmitters production in order to corroborate pathophysiological correlation of Nkx2.1, since some studies indicated the abnormalities of several neurotransmitters production in Nkx 2.1 deficient-mice in early development42, and also in adult mice3538. We found similar phenotype of neurotransmitters production in group 4 mice including increase of dopaminergic neurons and reduced GABAergic neurons (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Nkx2.1 is also known to be expressed in the hypothalamic region and periventricular areas from early phase of development to adult35. Further, Nkx2.1 is thought to play roles in puberty and reproductive function and schizophrenia353738. In humans, Nkx2.1 gene mutations can cause benign hereditary chorea (BHC)3940, a disease affecting the brain, lungs and thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is the homeobox motifs, enriched in both the LD and DD treatments, as well as around genes from clusters 1, 3, 4 and 5. Homeobox factors, in particular members of the NK homeobox gene family, with motifs enriched in both treatments, have been shown to contribute to rhythmic regulatory processes in mammals [25]. Within cluster 5, 16 cyclic genes, including NvClock (a core component of the circadian clock machinery), contain the binding motif of C/EBP in their accessible promoter region (Fig 3C and S3 Table).…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting finding is the presence (or absence) of homeobox-related TFs in rhythmic genes regulation. The identified motifs were enriched with NK Homeobox and HOX family motifs–some of which contribute to rhythmic regulatory processes [25] including CUX1 , LIN-39 ( HOX3A ), caudal and CDX2 (Caudal-Type Homeobox 2). Interestingly, caudal has also been identified (in gene cluster 3) and previously reported as a synchronizer of locomotor activity in crayfish [39].…”
Section: Discussionmentioning
confidence: 99%
“…New journals are dedicated to molecular psychiatry, for instance "Molecular Psychiatry" [18]. Mental illnesses are conceptualised as multi-organ, systemic illnesses involving a myriad of intra-and extracellular mechanisms [19,20]. The ambition to identify causal mechanisms connecting symptoms or syndromes with a neurobiological substrate remains central to the paradigm we are currently experiencing.…”
Section: Three Waves Of Biological Psychiatrymentioning
confidence: 99%